Long noncoding RNA MEG3 suppresses cell proliferation, migration and invasion, induces apoptosis and paclitaxel-resistance via miR-4513/PBLD axis in breast cancer cells. Issue 23 (1st December 2020) - Zhu, Mingzhi; Wang, Fang; Mi, Hailong; Li, Lin; Wang, Jing; Han, Mingli; Gu, Yuanting
ABSTRACT: Breast cancer remains a general-threat event in the health of women. Currently, increasing records indicate that long non-coding RNA maternally expressed 3 (MEG3) plays a central role in breast cancer. The current research focused on the function of MEG3 in paclitaxel (PTX)-resistance and human breast cancer growth. Levels of MEG3, microRNA (miR)-4513, and phenazine biosynthesis-like domain-containing protein (PBLD) were evaluated using quantitative real-time polymerase chain reaction (qRT-PCR) or western blot assays. 3-(4.5-dimethylghiazol-2-yl)-2, 5-diphenyltetrazolium Bromide (MTT) assay was performed to examine the IC50 of PTX and cell proliferation in breast cancer cells. In addition, cell apoptosis was determined utilizing flow cytometry. Transwell was conducted to assay cell migration and invasion in MCF-7 and MDA-MB-231 cells. The interaction between miR-4513 and MEG3 or PBLD was expounded via dual-luciferase reporter assay. Levels of MEG3 and PBLD were decreased, but miR-4513 level was triggered in breast cancer tissues and cell lines. Overexpression of MEG3 could reinforce cell apoptosis, impede proliferation, migration, invasion, and the IC50 of PTX in breast cancer cells. Moreover, the impact of miR-4513 inhibitor on cell progression and PTX-resistance was overturned by MEG3 deficiency. Interestingly, miR-4513 mimic could abolish the role of PBLD upregulation in cell behaviors and PTX-resistance in MCF-7 and MDA-MB-231 cells. Finally, the expression of PBLD was co-modulated by miR-4513 and MEG3 in vitro . MEG3/miR-4513/PBLD axis modulated PTX-resistance and the development of breast cancer cells, which might provide a promising therapeutic strategy for breast cancer.